Aberrant expression of CD5 in a B-lineage Acute Lymphoblastic Leukemia (ALL): a case report - Ni Ketut Puspa Sari; Ni Nyoman Mahartini; Ni Kadek Mulyantari; Anak Agung Ayu Lydia Prawita; Ni Komang Krisnawati; I Putu Yuda Prabawa; Sianny Herawati; Made Minarti Witarini Dewi; Ekarini Katharina Yunarti Nabu (Intisari Sains Medis, 2021)
Background: CD5 is expressed in several B-lymphocyte malignancies, including Chronic Lymphocytic Leukemia (CLL), Mantle Cell Lymphoma (MCL), but CD5 positive B-cell lineage Acute Lymphoblastic Leukemia (ALL) is extremely rare. Aberrant T-cell antigen expression is associated with poor prognosis and is a useful marker to identify patients at increased risk. This case report aims to elaborate on the aberrant expression of CD5 in B-lineage ALL.Case Presentation: A 16-years-old male presented with a history of gum bleeding and abdominal pain of 7 days with associated fever, weakness and bone pain of 2-month duration. The bone marrow aspiration showed lymphoblast 30 % with the positive vacuole. In addition, the immunophenotyping test indicates for leukemia B-lineage with expression CD19, CD10, HLA-DR, CD 34, and there is the aberrant expression of CD5.Conclusion: Aberrant expression CD5 in cases of ALL B lineage is very rare. This can be associated with a poor prognosis.